2014
DOI: 10.3390/su6085231
|View full text |Cite
|
Sign up to set email alerts
|

The Dynamic Coordinated Development of a Regional Environment-Tourism-Economy System: A Case Study from Western Hunan Province, China

Abstract: Based on regional coordination theory and system theory, the authors constructed an evaluation index system for the coordinated development of a regional environment-tourism-economy system with a pressure-state-response (PSR) model. With a coordinated development model, it further empirically analyzed the coordinated development state of an environment-tourism-economy system in western Hunan from 2001 to 2012. The results showed that, although this environment-tourism-economy system failed to achieve a high be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(36 citation statements)
references
References 12 publications
1
35
0
Order By: Relevance
“…From the time series data, disasters had been relatively well‐distributed in Yunnan, for both earthquakes (on average about 1,500 times a year, with the exception of 2014) and floods; earthquake magnitudes and disaster losses were also relatively regular and stable (Figures and ). The populations of foreign travelers could reflect this (Figure ), because travel is the response to domestic economic development and the ecological environment situation, which are very sensitive to natural disasters (Banday & Ismail, , Yuan, Jin, Ren, Hu, & Ren, ). Both the foreign traveler numbers and income from tourism have shown increasing trends since 2000 in Sichuan and Yunnan.…”
Section: Discussionmentioning
confidence: 99%
“…From the time series data, disasters had been relatively well‐distributed in Yunnan, for both earthquakes (on average about 1,500 times a year, with the exception of 2014) and floods; earthquake magnitudes and disaster losses were also relatively regular and stable (Figures and ). The populations of foreign travelers could reflect this (Figure ), because travel is the response to domestic economic development and the ecological environment situation, which are very sensitive to natural disasters (Banday & Ismail, , Yuan, Jin, Ren, Hu, & Ren, ). Both the foreign traveler numbers and income from tourism have shown increasing trends since 2000 in Sichuan and Yunnan.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, economic growth is the top contributor and the urbanization is the most significant factor in reducing carbon emission. Taking coordination and system theory into consideration, Yuan et al [34] empirically examined the coordinated growth of an environment-tourism-economy system in western Hunan from 2001 to 2012. The results confirmed that this system could not achieve the desired results for environmental improvements.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Wei et al studied the regional development differences of Jiangsu Province from 1950 to 1995 and believed that human capital, physical capital, and institutional structure were the main factors that caused regional development differences (Wei & Kim, 2002). Moreover, economic, ecological environment, and local government actions as well as innovation capacity, are also considered to affect regional coordinated development (Yang et al, 2014;Xu et al, 2011). The second stream focuses on the research perspective of coordinated regional development.…”
Section: Introductionmentioning
confidence: 99%